Hubungan Faktor Komunikasi dan Beban Kerja Terhadap Keselamatan Pasien Saat Bekerja di RSUD Kota Madiun - Astri Yunita; S Sumiati (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2022)
Patient safety according to the World Health Organization (WHO) is that there is no danger that threatens patients during the health care process. The purpose of the study was to analyze the relationship of communication factors and workload to patient safety in working at the Madiun City Hospital. Quantitative research design with analytical observational research methods with a cross-sectional approach. The population of all nurses at the Madiun City Hospital was 195 respondents. The sample of some nurses at the Madiun City Hospital was 131 respondents with purposive sampling. Independent variables of communication factors and workloads. Dependent variables of patient safety. The results showed that there was a relationship between the role of communication (p = 0.001) and workload (p = 0.042) to patient safety at work. It is hoped that nurses in providing health services must improve quality which will be able to provide comfort and quality services to patients in terms of improving patient safety.